PENGARUH MEDIA COLOUR CORRUGATED PAPER TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK IT AL-KAHFI INDRALAYA - Putri, Sabrina Amanda; Yin Yin Septiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of colour corrugated paper media on the fine motor skills of children aged 5-6 years at TK IT Al-Kahfi Indralaya. The research method used in this study is a quantitative Pre-experimental method with a one-shot case study design. While the data collection technique uses observation (Checklist sheet). The sample selection in this study used a cluster random sampling technique, namely 16 children aged 5-6 years consisting of 6 boys and 10 girls. The results of data analysis on the normality test that has been carried out show that the data is normally distributed because x² count ≤ x² table, namely x² count = 1.38 and x² table = 24.96 then from the t-test calculation it is obtained that t count = 5.01 and t table = 1.753. This shows that Ha is accepted and Ho is rejected, namely t count ≥ t table (5.01 ≥ 1.753). Therefore, the test results can be concluded that colour corrugated paper media has an effect on the fine motor skills of 5-6 year old children at Tk IT Al-Kahfi Indralaya.